2019
DOI: 10.18502/ijph.v48i5.1805
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Dual Practice in Surgery Specialists: Application of Multi-Level Analysis on National Registry Data

Abstract: Background: Dual practice by surgery specialists is a widespread issue across health systems. This study aimed to determine the level of dual practice engagement and its related factors among Iran’s surgery specialists. Methods: A pre-structured form was developed to collect the data about surgery specialists worked in all 925 Iran hospitals in 2016. The forms were sent to the hospitals via medical universities in each province. The data were merged at the national level and matched using medical council… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Medical specialists were more likely to participate in MJH, as reported in other studies 14 54. Similar to other studies,15 17 55 MJH was more likely to occur among doctors in urban GP 56. Nurses in management positions had a lower chance of engaging in MJH, as was also found in a study among nurses in China,57 and because they are assuming additional, complex roles58 that may limit the time for MJH.…”
Section: Discussionsupporting
confidence: 84%
“…Medical specialists were more likely to participate in MJH, as reported in other studies 14 54. Similar to other studies,15 17 55 MJH was more likely to occur among doctors in urban GP 56. Nurses in management positions had a lower chance of engaging in MJH, as was also found in a study among nurses in China,57 and because they are assuming additional, complex roles58 that may limit the time for MJH.…”
Section: Discussionsupporting
confidence: 84%
“…Working as a faculty member involves more research and educational activities; however, it is not usually accompanied by adequate income as they have less chance for dual practice compared with non-faculty surgeons. 6 We found that nearly 90% of the respondents dedicated less than two hours a week to research among which a huge proportion had no research activities. We found that shortage of time and lack of motivation was the cause in about 70% of the responses.…”
Section: Discussionmentioning
confidence: 74%
“…Extent. Five studies reported the rates of dual practice for general practitioners and medical specialists [5,11,12,15,21]. These rates were reported to be 18.65% for general practitioners working in both public or private sectors, 26.17% for general practitioners working in two or more job places (either public or private) [11], 57% for surgeons working in the public sector, 70% for non-full-time specialists in multiple job holdings, 58% for non-faculty member specialists in multiple job holdings, 69% for urinary tract and genital and neurosurgery [21], 63.1% for surgical specialists in other service locations [12], 47.7% for specialists in various medical specialties [15], and 42.3% for public medical specialists in the private sector [5].…”
Section: Main Themesmentioning
confidence: 99%